Fan and Regulators Fuzzy Control in Mine Ventilation Systems - Kashnikov, A. V.; Levin, L. Yu (2019 XXII International Conference on Soft Computing and Measurements (SCM), 2019)
Mine ventilation dynamic control contributes to a significant decline of operational expenditures. Applying of the fuzzy logic approach to ventilation equipment control is explained by nonlinear relationships between airflow distribution and fan and regulator operating parameters. The article describes mine ventilation system fuzzy control in a case of one main fan unit and several regulators.